Resection of the Portal-Superior Mesenteric Vein in Pancreatic Cancer: Pathological Assessment and Recurrence Patterns. Issue 8 (September 2021) - Groen, Jesse V.; van Manen, Labrinus; van Roessel, Stijn; van Dam, Jacob L.; Bonsing, Bert A.; Doukas, Michael; van Eijck, Casper H.J.; Farina Sarasqueta, Arantza; Putter, Hein; Vahrmeijer, Alexander L.; Verheij, Joanne; Besselink, Marc G.; et al.
Abstract : Supplemental digital content is available in the text. Abstract : Objectives: The portal vein (PV)-superior mesenteric vein (SMV) margin is the most affected margin in pancreatic cancer. This study investigates the association between venous resection, tumor invasion in the resected PV-SMV, recurrence patterns, and overall survival (OS). Methods: This multicenter cohort study included patients who underwent pancreatoduodenectomy for pancreatic cancer (2010–2017). In addition, a systematic literature search was performed. Results: In total, 531 patients were included, of which 149 (28%) underwent venous resection of whom 53% had tumor invasion in the resected PV-SMV. Patients with venous resection had a significant higher rate of R1 margins (69% vs 37%) and had more often multiple R1 margins (43% vs 16%). Patient with venous resection had a significant shorter time to locoregional recurrence and a shorter OS (15 vs 19 months). At multivariable analyses, venous resection and tumor invasion in the resected PV-SMV were not predictive for time to recurrence and OS. The literature overview showed that pathological assessment of the resected PV-SMV is not adequately standardized. Conclusions: Only half of patients with venous resection had pathology confirmed tumor invasion in the resected PV-SMV, and both are not independently associated with time to recurrence and OS. The pathological assessment of the resected PV-SMV needs to be standardized.